2012
DOI: 10.1128/jvi.01019-12
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Manipulation of a New Kaposi's Sarcoma-Associated Herpesvirus Bacterial Artificial Chromosome Clone

Abstract: Efficient genetic modification of herpesviruses such as Kaposi's sarcoma-associated herpesvirus (KSHV) has come to rely on bacterial artificial chromosome (BAC) technology. In order to facilitate this approach, we generated a new KSHV BAC clone, called BAC16, derived from the rKSHV.219 virus, which stems from KSHV and Epstein-Barr virus-coinfected JSC1 primary effusion lymphoma (PEL) cells. Restriction enzyme and complete sequencing data demonstrate that the KSHV of JSC1 PEL cells showed a minimal leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
455
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 313 publications
(473 citation statements)
references
References 79 publications
(101 reference statements)
8
455
0
Order By: Relevance
“…In contrast, KSHV expresses LANA in cis, and the generation of recombinant KSHV is much more limited with re-gard to the number of copies of genomes available for initial transfection or infection. In fact, these lower copy numbers of recombinant KSHV are similar to, or even higher than, the copy number of KSHV in vivo (64)(65)(66)(67)(68). Further, while the system used here may allow TR DNA to undergo extensive recombination to select episomes for increased episome maintenance efficiency, the virus does not have this luxury.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, KSHV expresses LANA in cis, and the generation of recombinant KSHV is much more limited with re-gard to the number of copies of genomes available for initial transfection or infection. In fact, these lower copy numbers of recombinant KSHV are similar to, or even higher than, the copy number of KSHV in vivo (64)(65)(66)(67)(68). Further, while the system used here may allow TR DNA to undergo extensive recombination to select episomes for increased episome maintenance efficiency, the virus does not have this luxury.…”
Section: Discussionmentioning
confidence: 92%
“…Telomerase-immortalized human umbilical vein endothelial cells (HUVECs) with KSHV infection (TIVE-KSHV cells) (77), KS tumor cells carrying the recombinant KSHV bacterial artificial chromosome 16 (BAC16) (iSLK-BAC16 cells) (76), and human embryonic kidney 293T cells were cultured in Dulbecco's modified Eagle medium (DMEM) plus 10% fetal bovine serum (FBS). KSHV-positive PEL cells (BCBL1 cells) (50) were grown in RPMI 1640 medium plus 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Our data demonstrated that the same region in KSHV ORF45 is involved in interaction with ORF33 and is critical for accumulation of ORF33 protein in cells. To determine the roles of this conserved region of ORF45 in KSHV lytic replication, we deleted the C-terminal 19 aa by introducing stop codons following leucine-389 of ORF45 in BAC16, an infectious bacterial artificial chromosome clone of the entire KSHV genome (39). Similarly, we repaired the mutations and created a revertant version of BAC16 (Fig.…”
Section: Identification Of Viral and Cellular Proteins Associated Withmentioning
confidence: 99%